Conceiving God: Literal and Figurative Prompt for a More Tectonic Distinction - Masson, Robert (Open theology, 2018)
John Sanders’ Theology in the Flesh, the first comprehensive overview of the toolkit that contemporary cognitive linguistics offers for theological appropriation, despite its remarkable success, gives rather minimal attention to blending theory, one of the discipline’s most formidable tools. This paper draws on blending theory to offer an alternative to Sanders’ chapter on conceiving God. Central to the proposal is claim that God-talk, like many of the advances in science, technology, and art, entails a kind of tectonic understanding and conceptual mapping that is neither literal nor figurative.